2000
DOI: 10.1016/s0008-6363(00)00010-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurally mediated depressor hemodynamic response induced by intracoronary catheter balloon inflation in pigs

Abstract: A depressor hemodynamic response subserved by pericoronary nerves worsens the LV dysfunction induced by brief coronary catheter balloon inflation in anesthetized pigs. Cholinergic fibers do not appear to play a major role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Sensory neurons are widely spread throughout the mammalian cardiovascular system and contain cardio-stimulatory neuropeptides. Among the neuropeptides, calcitonin gene-related peptide (CGRP), substance P and other neurokines play an intricate role in modulating cardiac function through local cardiac reflexes [9496]. CGRP release is regulated by multiple factors such as brief ischemia, hyperthermia or autocoids [9799].…”
Section: Circulating Mediators Of Ischemic Conditioningmentioning
confidence: 99%
“…Sensory neurons are widely spread throughout the mammalian cardiovascular system and contain cardio-stimulatory neuropeptides. Among the neuropeptides, calcitonin gene-related peptide (CGRP), substance P and other neurokines play an intricate role in modulating cardiac function through local cardiac reflexes [9496]. CGRP release is regulated by multiple factors such as brief ischemia, hyperthermia or autocoids [9799].…”
Section: Circulating Mediators Of Ischemic Conditioningmentioning
confidence: 99%
“…Thus, in balloon-induced coronary occlusion, there is vagal predominance, which can represent a beneficial adaptive mechanism to increase coronary blood flow during myocardial ischemia. Conversely, when coronary perfusion is deficient, an increase in sympathetic activity occurs 27-29 . In the present study, an increase in the LF and HF components was observed, with no significant change in the LF/HF ratio, during stent implantation, as compared with the values of those variables before and after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…One can find more than 100 references involving the use of CLS in this species in the open literature. It is an anaesthetic that is specifically recommended for the different fields of cardiovascular research (Bardaji et al, 1990;Benharkate et al, 1993;Cinca et al, 1996Cinca et al, , 2000Seaberg et al, 2001) and when the baroreflex should be conserved or studied (Svendsen, 1998;Wiklund et al, 2002). CLS produces minimal cardiovascular and respiratory system depression (Flecknell, 1987).…”
Section: Pressor Effects Of Na and Anaesthesiamentioning
confidence: 99%